Methionine sulfoxide reductases are essential for virulence of Salmonella typhimurium - Denkel, Luisa A.; Horst, Sarah A.; Rouf, Syed Fazle; Kitowski, Vera; Böhm, Oliver M.; Rhen, Mikael; Jäger, Timo; Bange, Franz Christoph (PLoS ONE, 2011)
Production of reactive oxygen species represents a fundamental innate defense against microbes in a diversity of host organisms. Oxidative stress, amongst others, converts peptidyl and free methionine to a mixture of methionine-S- (Met-S-SO) and methionine-R-sulfoxides (Met-R-SO). To cope with such oxidative damage, methionine sulfoxide reductases MsrA and MsrB are known to reduce MetSOs, the former being specific for the S-form and the latter being specific for the R-form. However, at present the role of methionine sulfoxide reductases in the pathogenesis of intracellular bacterial pathogens has not been fully detailed. Here we show that deletion of msrA in the facultative intracellular pathogen Salmonella (S.) enterica serovar Typhimurium increased susceptibility to exogenous H 2O 2, and reduced bacterial replication inside activated macrophages, and in mice. In contrast, a ΔmsrB mutant showed the wild type phenotype. Recombinant MsrA was active against free and peptidyl Met-S-SO, whereas recombinant MsrB was only weakly active and specific for peptidyl Met-R-SO. This raised the question of whether an additional Met-R-SO reductase could play a role in the oxidative stress response of S. Typhimurium. MsrC is a methionine sulfoxide reductase previously shown to be specific for free Met-R-SO in Escherichia (E.) coli. We tested a ΔmsrC single mutant and a ΔmsrBΔmsrC double mutant under various stress conditions, and found that MsrC is essential for survival of S. Typhimurium following exposure to H 2O 2, as well as for growth in macrophages, and in mice. Hence, this study demonstrates that all three methionine sulfoxide reductases, MsrA, MsrB and MsrC, facilitate growth of a canonical intracellular pathogen during infection. Interestingly MsrC is specific for the repair of free methionine sulfoxide, pointing to an important role of this pathway in the oxidative stress response of Salmonella Typhimurium. © 2011 Denkel et al.
Created from Fastlane, Scopus look-up